2021
DOI: 10.3390/cancers13133373
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Liquid Biopsy Biomarkers’ Clinical Utility in Diagnosis and Prognosis

Abstract: Prostate cancer (PCa) is the most common cancer in men worldwide. The current gold standard for diagnosing PCa relies on a transrectal ultrasound-guided systematic core needle biopsy indicated after detection changes in a digital rectal examination (DRE) and elevated prostate-specific antigen (PSA) level in the blood serum. PSA is a marker produced by prostate cells, not just cancer cells. Therefore, an elevated PSA level may be associated with other symptoms such as benign prostatic hyperplasia or inflammatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 101 publications
0
31
0
1
Order By: Relevance
“…Therefore, new methods for accurate risk stratification of prostatic nodules and reducing unnecessary biopsies are desirable to improve the management of PCa and patient prognosis. In recent years, non-invasive, cost-effective, high-accuracy liquid biopsy biomarkers such as DNA methylation have been developed for early diagnosis of PCa ( 36 ). However, liquid biopsy biomarkers still lack large-scale validation and have methodological and biological limitations, precluding implementation in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, new methods for accurate risk stratification of prostatic nodules and reducing unnecessary biopsies are desirable to improve the management of PCa and patient prognosis. In recent years, non-invasive, cost-effective, high-accuracy liquid biopsy biomarkers such as DNA methylation have been developed for early diagnosis of PCa ( 36 ). However, liquid biopsy biomarkers still lack large-scale validation and have methodological and biological limitations, precluding implementation in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that the PCA3 test ( 48 ) was the first urine biomarker test approved by the U.S. Food and Drug Administration (FDA) in 2012 for use in patients over the age of 50 with elevated sPSA levels and a history of negative prostate biopsy. Of men, the cutoff value was 25 to decide whether a repeat prostate biopsy was needed.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, another research group attempted to propose AQP5 as a prognostic biomarker by evaluating AQP5 expression in 60 prostate cancer specimens and prostate cancer cell lines. The result showed that 31.7% (19) patients exhibited high levels of AQP5 expression, 50.0% (30) showed intermediate, and 18.3% (11) showed absence of AQP5. Increased AQP5 expression frequently accompanies gene amplification associated with TNM stage and lymph node metastasis.…”
Section: Aquaporin Expression In Prostate Cancermentioning
confidence: 99%